2016
DOI: 10.3758/s13414-016-1084-9
|View full text |Cite
|
Sign up to set email alerts
|

Early attentional bias for negative words when competition is induced

Abstract: Previous research (Zeelenberg, Wagenmakers, & Rotteveel, 2006) revealed that emotionally meaningful words were identified significantly better than neutral words, with no difference between positive and negative words. Since in that study only a single target word was displayed at a time, we hypothesized that the equivalent performances for positive and negative words were due to a lack of competition. To test this, in our Experiment 1, we replicated Zeelenberg and colleagues' finding, using emotion-laden Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
(82 reference statements)
1
0
0
Order By: Relevance
“…They found that in the early processing stage of words, individuals showed attentional bias toward negative emotion-label words. These findings were supportive of the argument of Ho et al (2016) that when there was a competition between two stimuli, negative stimuli would capture attention earlier than positive or neutral ones and attract enhanced perception. An attentional bias toward negative emotion-label words instead of positive emotion-label ones was not observed in the ERP results, which was consistent with the findings of Zhang et al (2018) .…”
Section: Discussionsupporting
confidence: 83%
“…They found that in the early processing stage of words, individuals showed attentional bias toward negative emotion-label words. These findings were supportive of the argument of Ho et al (2016) that when there was a competition between two stimuli, negative stimuli would capture attention earlier than positive or neutral ones and attract enhanced perception. An attentional bias toward negative emotion-label words instead of positive emotion-label ones was not observed in the ERP results, which was consistent with the findings of Zhang et al (2018) .…”
Section: Discussionsupporting
confidence: 83%